A SUPPORTING AID FOR BEEF CATTLE INVESTMENT OF FARM HOUSEHOLD IN CENTRAL JAVA - Ekowati, T.; Darwanto, D.H.; Nurtini, S.; Suryantini, S. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
The research was conducted to analyze some factors influencing production, income, farmhousehold consumption and investment of farm household beef cattle in Central Java. Five districts werepurposively chosen for research location based on the number of beef cattle population, namelyRembang, Blora, Grobogan, Boyolali and Wonogiri. Forty respondents of each district were chosenrandomly using quota sampling. Data were analyzed through Simultaneous Regression and estimated byTwo Stage Least Square (TSLS). The results showed that independent variables were simultaneouslysignificant to dependent variables (production, income, farm household consumption and investment)with the Probability F test 0.0000 and adjusted R2 were 91%; 89%; 96%; 62%, respectively. Thesimulation’s analysis of agribusiness implementation consisted of 1) decreasing 15% of service perconception, 2) increasing of beef cattle breed and number of beef cattle 15% respectively, 3) raising ofprice of rice and number of household member 15% respectively and 4) increasing of income and priceof beef cattle 10% respectively influenced to farm household consumption and investment 0.446% and5.14%, respectively, meanwhile production and income did not change. The research can be concludedthat the independent variables simultaneously significant influenced to production, income, farmhousehold consumption and beef cattle investment. The simulation of changing usage of input factor andprice significantly influenced to farm household consumption and beef cattle investment.